2021
DOI: 10.7322/abcshs.2019136.1401
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of intestinal parasites in children from public preschool in the Triple Border Brazil, Argentina, and Paraguay

Abstract: Introdução: A prevalência de parasitoses em crianças de municípios brasileiros de fronteira é desconhecida. Objetivo: Identificar a prevalência de parasitos intestinais em crianças de pré-escola pública de fronteira brasileira e seu perfil socioeconômico e sanitário. Métodos: Foram obtidas amostras fecais de 178 crianças de Centro Municipal de Educação Infantil (CMEI) de Foz do Iguaçu, Brasil. As amostras foram processadas pelos métodos de sedimentação de Hoffman e centrifugação e flutuação no sulfato de zinco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
0
2
0
4
Order By: Relevance
“…In developing countries, low socioeconomic conditions are usually linked to gastrointestinal infections caused by parasites, viruses, and bacteria, especially during childhood (22,23). In this study, the analysis of the socioeconomic aspects of the children with diarrhea showed that they were from families with low educational and income levels, both variables usually associated with intestinal pathogen infections in children (23)(24)(25).…”
Section: Discussionmentioning
confidence: 65%
“…In developing countries, low socioeconomic conditions are usually linked to gastrointestinal infections caused by parasites, viruses, and bacteria, especially during childhood (22,23). In this study, the analysis of the socioeconomic aspects of the children with diarrhea showed that they were from families with low educational and income levels, both variables usually associated with intestinal pathogen infections in children (23)(24)(25).…”
Section: Discussionmentioning
confidence: 65%
“…Foz do Iguaçu é uma cidade brasileira, localizada em região de tríplice fronteira, está a cerca de 9,8 km de Ciudad Del Este (Paraguai) e a 15,1 km de Puerto Iguazu (Argentina), fato presente em poucos lugares no mundo (Foz do Iguaçu, 2021). A proximidade dos três países favorece a transmissão de doenças, particularmente do HIV/Aids, devido ao livre trafego de pessoas (Brasil, 2021), tornando assim, um importante local de investigação para a compreensão de doenças e suas consequências Peres et al, 2020;Ferreira et al, 2021).…”
Section: Discussionunclassified
“…As transformações epidemiológicas que o HIV vem apresentando no decorrer dos anos justificam a necessidade de conhecer o perfil epidemiológico e clínico de pacientes com HIV/Aids em cidades que apresentam altos índices da doença e do vírus. Diante deste contexto, Foz do Iguaçu, cidade fronteiriça brasileira têm sido um importante local de investigação para Research, Society and Development, v. 10, n. 16, e77101623316, 2021 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v10i16.23316 3 compreender doenças e seus efeitos na saúde humana Peres et al, 2020;Ferreira et al, 2021).…”
Section: Introductionunclassified
“…The available data on the frequency of E. vermicularis was derived from 25 studies that employed more than one technique, each based on different methodological principles 3,[12][13][14][20][21][22]25,29,[32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47] . Conversely, 29 studies utilized a single technique, either in isolation or in conjunction with helminth larvae concentration techniques 4,5,[7][8][9][10][11][15][16][17][18][19]23,24,[26][27][28]30,31,35,[48][49][50][51][52]…”
Section: Diagnostic Strategies For Enterobius Vermicularismentioning
confidence: 99%